Esophageal Intramural Pseudodiverticulosis and Concomitant Eosinophilic Esophagitis: A Case Series. (28th August 2016) - Scaffidi, Michael A.; Garg, Ankit; Ro, Brandon; Wang, Christopher; Yang, Tony T. C.; Plener, Ian S.; Grin, Andrea; Colak, Errol; Grover, Samir C.
Abstract : Background . Esophageal intramural pseudodiverticulosis (EIPD) is an idiopathic benign chronic disease characterized by flask-like outpouchings of the esophageal wall. It is unknown whether there is a genuine association between EIPD and eosinophilic esophagitis (EoE). Aims . To investigate a possible relationship between EIPD and EoE. Methods . Patients with radiographic or endoscopic evidence of pseudodiverticulosis were identified from the database at a single academic center. Cases were analyzed in three areas: clinical information, endoscopic findings, and course. Results . Sixteen cases of esophageal pseudodiverticulosis were identified. Five patients had histologic evidence of eosinophilic esophagitis. Patients with EoE had pseudodiverticula in the mid-to-distal esophagus while those with EIPD had pseudodiverticula predominantly in the proximal esophagus (p < 0.001 ). EoE with pseudodiverticulosis occurred in younger patients (p < 0.019 ). Food bolus obstructions were more common in patients with EoE and pseudodiverticulosis than in EIPD (p < 0.034 ). Conclusions . This is the first case series supporting a potential association between EoE and pseudodiverticulosis. We also identify characteristic features of pseudodiverticulosis that may raise clinical suspicion of underlying eosinophilic esophagitis.